ANALISIS PERLAKUAN ZAKAT ATAS PENGHASILAN DAN PENGHITUNGAN PENGHASILAN WAJIB PAJAK PRIBADI USAHAWAN MUSLIM DI KELURAHAN PAHLAWAN KECAMATAN KEMUNING DI PALEMBANG - Nia Andria Erzah (Al-Iqtishad: Jurnal Ekonomi Syariah, 2021)
Treatment of Zakat on Income in Calculation of Taxable Income for Individual Taxpayers of Muslim Entrepreneurs in the Kelurahan Pahlawan According to the Decree of the Director General of Taxes Number KEP-163/PJ/2003, the reduction of zakat on income is permitted if it is actually paid by the Individual Taxpayer who is a Muslim and or domestic corporate taxpayers owned by Muslims. Impact of Zakat Treatment on Income in Calculation of Taxable Income on Income Tax Revenue The implementation of income zakat as a deduction from Taxable Income will clearly have a direct effect on government revenues from the tax sector. However, at the Palembang Tax Service Office, this influence does not yet exist. Because there is no supervision on the zakat paid by taxpayers, especially WP OP Muslim entrepreneurs in the Palembang village. SelPain means that zakat payments should be distributed to amil zakat institutions established by the government to be able to carry out zakat treatment in calculating PKP. However, Muslim entrepreneurs in the Pahlawan village distribute their zakat to mosques or directly to those they think are entitled to receive them. This resulted in the amil zakat agency or amil zakat institution not receiving zakat from muzakki entrepreneurs in the Pahlawan village.